Menilik Jejak Historis Pendidikan IPS Di Indonesia: Konsep Dan Kedudukan Pendidikan IPS Dalam Perubahan Kurikulum Di Sekolah Dasar - Ashar Pajarungi Anar; Arif Widodo; Dyah Indraswati (Phinisi Integration Review, 2022)
Social studies education is one of the compulsory subjects in elementary schools. At the elementary school level, social studies need to be taught because it contains material that teaches about social interaction as a provision for students to be able to socialize, communicate and collaborate as part of community members. The scope of Social Studies which studies humans, space, and time as well as change and continuity has the aim that students can develop values, attitudes, and skills both as individual beings and as social beings. The main purpose of social studies education is to equip students to be able to play a role as good citizens in their daily lives. By studying social studies students are expected to have awareness and concern for social issues and problems, as well as be able to make critical analyses and be able to take appropriate action to resolve them. Social studies education in its development does not escape changes, both in terms of the organization of learning materials and learning techniques. These changes are a consequence of changes in the learning curriculum which is always updated according to the demands of the times. Through a search of various relevant literature in this article, we will review how the concept, history, and position of social studies education in the learning curriculum in elementary schools.